A többször jubiláló 50 éves Nyíregyházi Főiskola - Brezsnyánszky, László (Gerundium, 2018)
THE 50-YEAR-OLD NYÍREGYHÁZA COLLEGE WITH MULTIPLE ANNIVERSARIES. he essay ofers a short review of the history of the Nyíregyháza College which has several predecessors during its existence, raising the question when and how an institute with at least three predecessors and with multiple functions can celebrate its anniversary? he writing introduces the anniversary celebrations from 2009, 2011 and 2012 and the related publications.